Bio-inspired information and communication technologies : 11th EAI International Conference, BICT 2019, Pittsburgh, PA, USA, March 13-14, 2019, proceedings /: 11th EAI International Conference, BICT 2019, Pittsburgh, PA, USA, March 13-14, 2019, proceedings. (2019) - Unknown
No abstract available